PERAN PENDIDIKAN GEOGRAFI DALAM KEBIJAKAN PEMBANGUNAN PERTANIAN BERKELANJUTAN: TINJAUAN LITERATUR - Melda Yulisa; Mazwan; Muis; Aprianty; Heri Akmal; Kartika Selytias Utami; Faraisha Hizra; Ulia Safitri; Siti Shara (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Sustainable agricultural development is a strategic agenda in Indonesian public policy, given the agricultural sector's role in maintaining food security, environmental balance, and public welfare. Geography education plays a crucial role in developing the spatial, ecological, and regional understanding needed for the formulation and implementation of agricultural policies. This article aims to examine the role of geography education in supporting sustainable agricultural development policies through a literature review approach. The research method used is a literature review of national and international journal articles relevant to geography education, public administration, and agricultural development. The results of the study indicate that geography education plays a role in strengthening the capacity for spatial analysis of agricultural policies, increasing the environmental literacy of policymakers and the public, and supporting regional-based agricultural planning. This article concludes that integrating geography education into public policy can be an important strategy for realizing sustainable and equitable agricultural development.